PENERAPAN METODE BUZZ GROUP UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID KELAS XI SMA PGRI PEKANBARU - Kartika Rahayu; Betty Holiwarni; Susilawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research on the use Buzz Group method have been done to find outhow it affect the student achievement on the topic of colloid in class XI IPA SMA PGRIPekanbaru. This kind of research is experiment research with randomized controlgroup pretest-posttest design. The sample consisted of two classes, namely class XIIPA-1 as the experimental class and class XI IPA-2 as a controls class, it randomlyselected after normality test and homogeneity test. Experimental class is a class thatwas treated by learning using method Buzz Group, while the control class is a class thatis not treated using Buzz Group method. Data analysis technique is the t-test. Based onthe final calculation result obtained tvalue is 3,104 is greater than ttable is 1.67 with anincrease in the use of media influence a Buzz Groups method to student achievement is10,38%, so it can be concluded that the use of the Buzz Group method can improve thestudent’s achievement on the subject of colloid in class XI Science high School PGRIPekanbaru.Key Words: Buzz Group method, Achievement Learn